Biological macromolecules from algae and their antimicrobial applications - Natanamurugaraj, Govindan; Maniam, Gaanty Pragas; Mohd Hasbi, Ab. Rahim; Ahmad Ziad, Sulaiman; Azilah, Ajit (Science Direct, 2021)
Algae are the dominated diverse group of the unicellular and multicellular organisms in the eukaryotic phylum. They have close resemblance with photosynthetic plants in the form of metabolic pathways, but the actual root systems are not similar. Microalgae can be cultivated using natural or artificial light systems using freshwater, marine water blackish water and even wastewater providing additional benefit by removing nutrients and organic pollutants from wastewater. Peptides (BP) are specific protein fragments that are involved in a wide range of therapeutic activities as antihypertensive, antioxidant, antitumoral, antiproliferative, hypocholesterolemic, and antiinflammatory. Besides, their also involved triggering mechanisms as well as nutritive function that providing the amino acid units as building blocks for new proteins to cells. Microalgae antimicrobial peptides (AMPs) have several advantages including gene expression similar to higher plants and cost effective phototrophic cultivation with simple and inexpensive medium and a safe food additive, so oral delivery of AMPs containing algae is possible.